Consensus SEO-SEFH of recommendations for use and compounding of ophthalmic preparations - Raquel Fuentes-Irigoyen; Ana María Martín de Rosales Cabrera; Ana Cristina Riestra; María Nieves Vila; Carmela Dávila-Pousa; José María Alonso Herreros; Carmen López-Cabezas; Carmen Cañete; María Sagrario Pernía-López; Marta Garcia-Palomo; Pedro Arriola Villalobos; Lucía Ibares-Frías; et al. (Farmacia Hospitalaria)
Abstract: There are many medicinal products that, although having shown efficacy and safety in different ophthalmological indications, they are not authorized or commercially available for ophthalmic administration. This implies, on one hand, that they must be used according to legislation that regulates the availability of medicines in special situations and, on the other hand, that they must be prepared in the pharmacy services for ophthalmic administration, according to quality criteria to ensure its effectiveness, stability and sterility. This document gathers the consensus between the Spanish Society of Ophthalmology and the Spanish Society of Hospital Pharmacy about these selected preparations which have shown enough evidence in their efficacy and safety for their ophthalmic use (off label) and ophthalmic administration. This document includes recommendations about its use according to the current legislation. In addition, with the aim of harmonizing the preparation of intraocular injections in the hospital pharmacy services, general recommendations are set in this document to ensure the compliance with standards established in the Spanish Guideline for Good Preparation Practices of Medicinal Products in Hospital Pharmacies. These recommendations include sections such as the area of preparation, material, technique, packaging, stability, quality control, prescription and traceability of intraocular preparations.